Study on Drag Coefficient (CD) value of low-energy prototype class car / J. Jodiputra...[et al.] - J., Jodiputra; S., Tobing; H., Gunawan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Researches on car design are closely related to the field of aerodynamics. The design was done to minimize the drag force. The experimental method was only used for testing the initial design and the final design. Improvement and modification were done by using the CFD simulation. The experiments were done using the Low Speed Wind Tunnel (LSWT) owned by the National Laboratory for Aerodynamics, Aeroelastics, and Aeroacoustics Technology. The Reynolds number ranged from 505,225 to 671,528. The research began with the initial design called JM-5, tested in the LSWT. Modifications were done throughout the research to achieve the lowest drag coefficient value. In the end, JM-4v2 became the final design with the lowest drag coefficient value of 0.202.